Exploring Wèwèkas and Ipat-Ipat attributed to Sunan Gunung Djati: Insights from the Sajarah Peteng Manuscript - Hernawan, Wawan (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
This study examines the Wèwèkas and Ipat-ipat attributed to Sunan Gunung Djati found in the Sajarah Peteng manuscript by Kyai Mas Ragil, Keragilan-Cirebon. The grains of Wèwèkas and Ipat-ipat are scrutinised for their meaning to be understood by today's people. This research employs qualitative and non-hypothetical methods. Text analysis was used in this research, with the stages including manuscript inventory, manuscript description, script translation, and language translation. The results showed that Sunan Gunung Djati's Wèwèkas and Ipat-ipat are found in macapat pangkur dangding one to 14. The conclusions of this study show that from 14 dangding there are 25 Wèwèkas and 15 Ipat-ipat. As for the meaning, seven contains messages related to the divine and the relationship between creatures and the sacred. The remaining 33 Wèwèkas and Ipat-ipat are about human relationships. They contain advice on life practices full of basic and universal human values. Secondly, when presenting Wèwèkas and Ipat-ipat, Sunan Gunung Djati included rewards and punishments for those who succeeded in carrying out Wèwèkas while avoiding Ipat-ipat. This research is expected to provide valuable insights into understanding spirituality, culture, and local wisdom in Indonesia that remain relevant today.